AVALIAÇÃO CLÍNICA DA EFETIVIDADE E GENOTOXICIDADE DO PERÓXIDO DE CARBAMIDA 10% EM PACIENTES FUMANTES - Geus, Juliana Larocca de (2014)
The aim of this study was to clinically evaluate the effectiveness, stability of color, dental sensitivity and genotoxicity of at-home bleaching with 10% carbamide peroxide (CP) in smokers and nonsmokers. For this study, two experiments were conducted. In Experiment 1 were selected 60 patients with central incisors A2 or darker, compared to Vita classical shade guide (Vita Zahnfabrik, Bad Säckingen, Germany), 30 smokers (S- experimental group) and 30 non-smokers (NS - control group). The bleaching was carried out with 10% CP (Whiteness Perfect, FGM, Joinville, Santa Catarina, Brazil) for a period of 3 hours daily for three weeks.The color was assessed by Vita classical (Vita Zahnfabrik, Bad Säckingen, Germany) and spectrophotometer Vita Easyshade (Vita Zahnfabrik, Bad Säckingen, Germany) initially during bleaching (1st, 2nd and 3rd weeks) and after this procedure (1 week and 1 month). The tooth sensitivity was recorded by the patients, using a 0-4 scale and visual analogue scale (VAS) of 10 cm. The Experiment 2 was conducted in the same sample of Experiment 1. The color was evaluated using Vita Bleachedguide 3D-MASTER (Vita Zahnfabrik, Bad Säckingen, Germany) in the same periods that Experiment 1. The genotoxicity of bleaching was evaluated by the frequency of micronuclei (MN) in the gingival tissue before and after bleaching. Data from two experiments were evaluated by analysis of variance two-factor repeated measures and Tukey's test for contrast of means (α=0.05). Data from ΔSGU and ΔE showed an effectiveness of dental bleaching in both groups after three weeks of treatment.The prevalence of tooth sensitivity was similar between groups. The frequency of MN in the experimental group was significantly higher than in the control group regardless of bleaching treatment. It can be concluded that the effectiveness of bleaching and tooth sensitivity resulting from the procedure does not seem to be affected by smoking and dental bleaching with 10% carbamide peroxide can be considered a safe procedure.